Agrarian budget as an instrument of agrarian development policy of Serbia - Kardovic , Danko (Applied Studies in Agribusiness and Commerce, 2009)
Purpose of the research is to emphasize the role of agrarian budget in development of Serbian agrarian economy and to examine the problem of agricultural and rural development financingsupport.Furthermore, in this research initial reforms of economic measures have been analyzed concerning Serbian agrarian policy. The goal of this paper is to provide an insight into the role of agricultural budget in agrarian policy of Serbia.The first part of the study gives an overview of macroeconomic situation in Serbia and impact of the financial crisis on Serbia’s economy. Second part includes analysis of the topic item, i.e. agrarian budget role in Serbian agrarian sector. It includes review of relevant literature and researches already conducted on legislation and practice of Serbian agrarian policy as well as examination of statistical data regarding present agrarian budget for 2009.The research focuses at the Serbian agrarian budget for 2009 and agrarian policy of the present Serbian government administration.